Kepastian Hukum Permohonan Penetapan Hak Perwalian Anak oleh Orang Tua Kandung - Vinanda Prameswati; Trisadini Prasastinah Usanti; Erni Agustin (Fakultas Hukum Universitas Airlangga, 2024)
District Court Judges and Religious Court Judges in resolving child guardianship cases often issue different decisions regarding the same legal event, some reject the guardianship application, others accept the guardianship application, this shows that legal certainty has not been achieved in resolving guardianship application cases. The type of research used in this research is normative juridical with a statutory approach, a conceptual approach and a case approach. The results of this research show that child guardianship can occur when there is a legal event such as both of the child's parents die, parental authority is revoked, or the child's whereabouts are unknown, and/or both parents are unable to carry out their obligations and responsibilities towards the child. this is as regulated in Article 50 paragraph (1) of the Marriage Law, Article 3 paragraph (1) PP No. 29 of 2019, as well as Article 33 paragraph (1) of the Child Protection Law. Furthermore, there are inconsistencies in the determination of guardianship determined by District Court judges and Religious Court Judges in the event of legal events of buying and selling, divorce, and the death of one of a child's biological parents, because each judge relies on different rules such as BW, Marriage Law, Child Protection Law and regulations in the form of KHI.